Explanations and information-giving: clinician strategies used in talking to parents of preterm infants. Issue 1 (December 2016) - Redshaw, M.; Harvey, M.
Abstract Background The study is part of a larger research programme on neonatal brain imaging in the trial element of which parents were randomised to receive prognostic information based upon either magnetic resonance imaging (MRI) or ultrasound findings (ePrime study). The aim of this study was to investigate the strategies used by clinicians in communicating with parents following imaging at term age of the brain of preterm infants born before 33 weeks gestation, focusing on explanations and information-giving about prognosis Method Audio recordings of discussions between parents and clinicians were made following MRI and ultrasound assessment. Parents were given the scan result and the baby's predicted prognosis. A framework was developed based on preliminary analysis of the recordings and findings of other studies of information-giving in healthcare. Communication of scan results by the clinicians was further explored in qualitative analysis with 36 recordings using NVivo 10 and the specifically developed framework. Emerging themes and associated sub-themes were identified. Results The ways in which clinicians gave information and helped parents to understand were identified. Within the over-arching theme of clinician strategies a wide range of approaches were used to facilitate parental understanding. These included orienting, checking on previously acquired information, using analogies, explaining terminology, pacing the information, confirming understanding, inviting clarification, answering parents' questions and recapping at intervals. Ultimately four key themes were identified: 'Framing the information-giving', 'What we are looking at', 'Presenting the numbers and explaining the risk' and 'Appreciating the position of parents'. Conclusions The interviews represent a multifaceted situation in which there is a tension between the need to explain and inform and the inherent complexity of neurological development, potential problems following preterm birth and the technology used to investigate and monitor these.